Category of Terrible in the Tale and the Ethnic and Cultural Education in Kindergarten - Elena A. Samodelova (Publishing house "Sreda", 2019)
Relatives of child told him the tales before appearance the kindergartens as special institutions, and then the role of this narrators was passed on the kindergarten teachers, which were standing to read the folk and author's work on books. The aim of paper is to show, how the replacement of the environment from home to official substantially changes the perception by child of the tales, and the pedagogues must select the recitation especially carefully. Methods: brief historical survey about the features of the existence of folktales in patriarchal social environment gave; and the comparison with firsthand acquaintance of children with tales at present conducted. Result: the folktales were created in archaistic epoch and that is why not correspond with modern ethical standards. And even author's tales of the classical writers, that were built on folktales, inherited many their traits, including the mention about cruelty. Come to the conclusion that the componentry of aesthetics of terrible contain in the folktales and are able to hurt the immature child's soul.